The impact of the COVID-19 pandemic on the global burden of type 2 diabetes: a study based on GBD 2021 data - Chen, Xiaoqin; Lin, Hui; Wu, Yinlian; Wang, Mingfang; Lin, Su; Huang, Jiaofeng (Frontiers in Endocrinology, 2025)
BackgroundThis study aimed to comprehensively assess the impact of the coronavirus disease 2019 (COVID-19) pandemic on the global burden of type 2 diabetes mellitus (T2DM) using data from the Global Burden of Diseases (GBD) 2021.MethodsAge-standardized T2DM prevalence, incidence, mortality, and disability-adjusted life years (DALYs) were analyzed from Global Burden of Diseases (GBD) 2021. Pre-pandemic (2010–2019) and post-pandemic (2020–2021) periods were defined to capture pandemic onset, with 2020–2021 as the earliest available global post-pandemic data. Expected annual percentage changes (EAPC) were derived to assess the magnitude and direction of trends over the study period, adjusting for age, sex, and sociodemographic index. Post-pandemic projections to 2030 employed a Bayesian model with pre-/post-pandemic slope comparisons.ResultsGlobal T2DM prevalence (ages ≥20) rose from 6,887.07 per 100,000 in 2010 to 9,545.42 per 100,000 in 2021. Post-pandemic acceleration was observed: EAPC increased from 2.90% (95% CI: 2.86–2.94) pre-pandemic to 3.52% (95% CI: 3.14–3.90) post-pandemic. Mortality and DALYs showed similar accelerations. Despite continued increases in incidence, mortality, and DALYs, the EAPC decreased in the post-pandemic period. Projections using pre-pandemic data (up to 2019) estimated type 2 diabetes prevalence at 10368.23 per 100,000 population by 2030. However, incorporating post-pandemic data (up to 2021) increased the projected 2030 prevalence to 10694.79 per 100,000, indicating a rise of 326.56 per 100,000 attributed to the pandemic’s impact. The prevalence, incidence, deaths, and DALYs of CKD due to T2DM all showed an upward trend from 2010 to 2021.ConclusionsA rapid increase in the burden of T2DM is found post-COVID-19 pandemic. Enhanced public health interventions are required for the prevention, screening, and management of diabetes.